Mars Initial Reference Ionosphere (MIRI) Model: Updates and Validations Using MAVEN, MEX, and MRO Data Sets. Issue 7 (4th July 2018) - Mendillo, Michael; Narvaez, Clara; Trovato, Jeffrey; Withers, Paul; Mayyasi, Majd; Morgan, David; Kopf, Andrew; Gurnett, Donald; Němec, Frantisek; Campbell, Bruce
Abstract: The Mars Initial Reference Ionosphere (MIRI) model is a semiempirical formulation designed to provide climatological estimates of key parameters of the Martian ionosphere. For the new MIRI‐2018 version, an expanded database is used from the Mars Express/Mars Advanced Radar for Subsurface and Ionosphere Sounding/Active Ionospheric Sounding (MEX/MARSIS/AIS) instrument, consisting of 215, 818 values of maximum electron density of the M2‐layer (Nm M2 ) from the years 2005–2015. These data are organized by photochemical‐equilibrium equations to obtain a functional dependence of Nm M2 upon solar drivers (flux and solar zenith angle). The resulting peak density is used to calibrate normalized electron density profiles [ N e ( h )] derived from theory and an empirical model. The MIRI‐2018 thus provides estimates of Nm M2, N e ( h ), and total electron content (TEC) for any date past or future. Validation using Mars Atmosphere and Volatile EvolutioN (MAVEN)'s new radio occultation science experiment (ROSE) was successful for Nm M2 values, but MIRI was found to overestimate TEC values. The validation failure for TEC was traced to overestimates of plasma at low altitudes (M1 layer). A separate module for TEC was derived using 126, 055 values from the Mars Reconnaissance Orbiter/SHAllow RADar (MRO/SHARAD) TEC database from 2006 to 2014. Validation of this new TEC module with ROSE data was successful. Future improvements to MIRI‐2018 require new ways to characterize the bottomside ionosphere's contribution to the TEC integral for midday (low solar zenith angle) conditions. This requires new simulation studies of secondary ionization rates by photoelectrons produced via the primary X‐ray ionization process for the M1 layer. Key Points: Scientific understanding of complex ionospheric patterns and processes at Mars requires a baseline specification model New methods of daily predictions for maximum electron density and total electron content are derived and tested using new data sets Validation issues for midday conditions require more accurate theoretical calculations of X‐ray produced secondary ionization rates